Use of a Gelatin-Thrombin Hemostatic Matrix for Secondary Bleeding After Pediatric Tonsillectomy - BİNNETOĞLU, ADEM; YUMUŞAKHUYLU, ALİ CEMAL (AMER MEDICAL ASSOC, 2016)
IMPORTANCE Secondary posttonsillectomy bleeding associated with oozing from multiple sites or overcauterized tonsillar bed deserves special evaluation. OBJECTIVE To evaluate the use of an absorbable, flowable gelatin-thrombin hemostatic matrix (GTHM) sealant for secondary bleeding after tonsillectomy. DESIGN, SETTING, AND PARTICIPANTS This was a retrospective data analysis, with information gathered from medical records of pediatric patients with secondary posttonsillectomy bleeding treated with the GTHM between 2012 and 2016 at a referral center and a local satellite facility. Forty-two pediatric patients admitted with secondary bleeding after tonsillectomy characterized by diffuse bleeding, multiple bleeding sites, or an overcauterized tonsillar bed, were treated with GTHM. Exclusion criteria were a bleeding disorder, genetic syndrome associated with abnormal oropharyngeal anatomy, and hemorrhage from a single site. EXPOSURES GTHM was used to treat posttonsillectomy secondary bleeding. MAIN OUTCOMES AND MEASURES Patient medical records were reviewed for information relevant to this study: (1) patient history, the tonsillectomy surgical technique used, and whether there were prior bleeding episodes (and if so, methods of treatment); (2) physical examination and laboratories on presentation, operative report details, and results of treatment; (3) hospital course and whether any further bleeding episodes occurred; and (4) hospital follow-up information (range, 3-20 months). RESULTS The study population comprised 22 boys (52%) and 20 girls (48%) (a total of 42 patients), and the mean (SD) age was 7 (2.7) years (range, 4-14 years). Two patients had presented with recurrent secondary bleeding necessitating multiple operations, but the others had only 1 episode. The mean day of occurrence of bleeding was on the eighth day (range, day 7-12; median, day 10). Only 2 patients required blood transfusions: they were the same patients who underwent multiple operations for recurrent episodes of secondary bleeding. All patients except for 1 (41 of 42) were discharged without further bleeding following treatment. No adverse effects were reported. CONCLUSIONS AND RELEVANCE Results suggest that GTHM is generally simple, safe, and effective for use in the treatment of posttonsillectomy secondary bleeding types not associated with a direct vein or artery source but oozing from multiple sites and/or overcauterized tonsillar bed that cannot be stopped by traditional hemostatic methods.
Keywords: RANDOMIZED CONTROLLED-TRIAL; CONTROLLED CLINICAL-TRIAL; DISSECTION TONSILLECTOMY; SURGERY; AGENT; CHILDREN; SEALANT; FLOSEAL; ADENOIDECTOMY; MULTICENTER